Combination therapy with radiation and hyperthermia‐induced clinical complete response of small cell carcinoma of prostate. Issue 2 (14th January 2022) - Kawai, Noriyasu; Nagai, Takashi; Naiki‐Ito, Aya; Iida, Keitaro; Etani, Toshiki; Naiki, Taku; Hamamoto, Shuzo; Okada, Atsushi; Murai, Taro; Yasui, Takahiro
Abstract : Introduction: Small cell carcinoma of the prostate has a poor prognosis even with standard systemic chemotherapy. We report a case, in which combination therapy with radiation and hyperthermia‐induced clinical complete response. Case presentation: An 87‐year‐old man complaining of dysuria was referred to our hospital. Based on magnetic resonance imaging findings and a history of prostate cancer, a prostate biopsy was performed, and small cell carcinoma of the prostate was diagnosed. Whole‐pelvis radiation therapy was administered with an additional dose to the prostate; eight cycles of hyperthermia treatment (8 MHz radiofrequency capacitive regional hyperthermia) were administered concurrently. Normalized neuron‐specific enolase levels and magnetic resonance imaging confirmed a complete response. A few cancer cells were seen in the post‐treatment biopsy specimen, which demonstrated positive immunostaining for heat shock protein 70 and HIKESHI. Conclusion: In this case, small cell carcinoma of the prostate was effectively treated with combined radiation and hyperthermia therapy.